Predictors associated with malocclusion in children with and without sleep disorders: a cross-sectional study - Gélica Lima GRANJA; Tiago Ribeiro LEAL; Larissa Chaves Morais de LIMA; Samara Ellen da SILVA; Érick Tássio Barbosa NEVES; Fernanda Morais FERREIRA; Ana Flávia GRANVILLE-GARCIA (Sociedade Brasileira de Pesquisa Odontológica, 2023)
Abstract The aim of the present study was to investigate predictors of malocclusion in Brazilian schoolchildren eight to ten years of age based on a causal directed acyclic graph model. A cross-sectional study was conducted with 739 schoolchildren eight to ten years of age. Parents/guardians provided information on sleep disorders of the child (Sleep Disturbance Scale for Children) and family characteristics (Family Adaptability and Cohesion Evaluation Scale). The diagnosis of malocclusion was performed by four trained examiners using the Dental Aesthetic Index. Control variables were selected using a directed acyclic graph. Descriptive analysis was performed, followed by robust logistic regression analysis for complex samples (α = 5%). The following variables were associated with malocclusion in the final model: sleep disorders (OR = 2.61; 95%CI: 2.43-2.86), mouth breathing (OR = 1.04; 95%CI: 1.02-1.99), non-nutritive sucking habits (OR = 2.45; 95%CI: 2.37-4.85), and obesity (OR = 1.54; 95%CI: 1.02-2.33). Sociodemographic characteristics, family functioning, and premature tooth loss did not remain associated with malocclusion. Sleep disorders, mouth breathing, sucking habits, and obesity are predictors of malocclusion in schoolchildren eight to ten years of age.